Positive Valence Bias in L2 Vocabulary Acquisition: Evidence From Chinese Emotion Idioms - Wang, Mengxing; Li, Li; Xie, Jiushu; Wang, Yaoyao; Chen, Yao; Wang, Ruiming (Frontiers in Psychology, 2022)
Positive valence bias refers to speakers responding faster to positive than negative information in L2 emotion words. Few researchers paid attention to the initial learning phase of L2 Chinese emotion idioms in which whether positive valence bias was acquired, based on the three-stage model of L2 vocabulary acquisition. Besides, whether the semantic information would modulate positive valence bias at the initial learning phase remained unclear. This study reports two experiments on speakers learning Chinese as a second language (CSL) to investigate positive valence bias in the initial learning phase of new Chinese emotion idioms and the modulation of semantic information on positive valence bias. Chinese as a second language speakers, who had acquired new Chinese emotion idioms and passed the test for learned Chinese idioms with a high accuracy rate before formal experiments, participated in Experiments 1 and 2. In Experiment 1, target materials were new Chinese idioms with positive and negative information. Positive valence bias at the initial learning phase of Chinese idioms was investigated with valence judgments. Experiment 2 used a semantic relatedness decision task further to explore the semantic effect on positive valence bias. The result in the first experiment showed that positive valence bias appeared in Chinese emotion idioms even at the initial learning phase of the acquisition. Meanwhile, semantic information of Chinese emotion idioms appeared to affect positive valence bias in the infant learning phase in Experiment 2. The findings revealed that semantic information would affect the performance of positive valence bias, suggesting that the semantic processing would automatically access the valence at the infant learning phase L2 Chinese emotion idioms. The research results provided evidence that positive valence bias would form in the infant learning phase of Chinese emotion idiom acquisition, based on the L2 vocabulary acquisition model.